Sustainable Reporting and Profitability of Quoted Firms in Nigeria: A Multi-Dimensional Panel Data Study - Iheduru, Ngozi G.; Okoro, Charles U. (Australian Finance & Banking Review, 2019)
This paper used cross sectional data to examine the effect of sustainable reporting on the profitability indicators of Nigeria quoted firms between 2008-2017. Data was sourced from financial statement of the firms. Twenty firms were selected from the population of quoted firms in Nigeria. Return on equity, earnings per share and return on investment were proxy for profitability while sustainable reporting was proxied by economic, social, environmental and corporate governance disclosure. The panel data model was tested using the Hausman test. Model one and two validated the fixed effect while model three validated the random effect. The results found that economic disclosure and social disclosure have positive but insignificant effect on return on equity of the selected firms while environmental and corporate governance disclosure have negative and insignificant effect on return on equity, all the predictor variables have positive and insignificant effect on earnings per share of the firms and that economic, social and environmental disclosure have positive effect on return on investment while corporate governance disclosure have negative effect on return on investment of the selected firms in Nigeria. We recommend that operating environment of the firms should be well examined and policies should be advanced to manage factors such as economic, social, environmental and corporate governance disclosures to leverage the environmental challenges and enhance profitability, companies should ensure strict compliance to all forms of sustainability reporting.